Manipulation of magnetic vortex parameters in disk-on-disk nanostructures with various geometry - Stebliy, Maxim E.; Kolesnikov, Alexander G.; Ognev, Alexey V.; Samardak, Alexander S.; Chebotkevich, Ludmila A. (Beilstein Journal of Nanotechnology, 2015)
Magnetic nanostructures in the form of a sandwich consisting of two permalloy (Py) disks with diameters of 600 and 200 nm separated by a nonmagnetic interlayer are studied. Magnetization reversal of the disk-on-disk nanostructures depends on the distance between centers of the small and big disks and on orientation of an external magnetic field applied during measurements. It is found that manipulation of the magnetic vortex chirality and the trajectory of the vortex core in the big disk is only possible in asymmetric nanostructures. Experimentally studied peculiarities of a motion path of the vortex core and vortex parameters by the magneto-optical Kerr effect (MOKE) magnetometer are supported by the magnetic force microscopy imaging and micromagnetic simulations.
Keywords: hysteresis; magnetic vortex; magnetization reversal; micromagnetic structure

(untitled) - Coffey, W. T.; Kalmykov, Y. P. (J. Appl. Phys., 2012)

(untitled) - Guslienko, K. Yu.; Novosad, V.; Otani, Y.; Shima, H.; Fukamichi, K. (Phys. Rev. B, 2001)

(untitled) - Kikuchi, N.; Okamoto, S.; Kitakami, O.; Shimada, Y.; Kim, S. G.; Otani, Y.; Fukamichi, K. (J. Appl. Phys., 2001)

(untitled) - Zhong, Z.; Zhang, H.; Tang, X.; Jing, Y.; Jia, L.; Liu, S. (J. Magn. Magn. Mater., 2009)

(untitled) - Dumas, R. K.; Gredig, T.; Li, C.-P.; Schuller, I. K.; Liu, K. (Phys. Rev. B, 2009)

(untitled) - Cambel, V.; Karapetrov, G. (Phys. Rev. B, 2011)

(untitled) - Liu, Y.; Du, A. (J. Appl. Phys., 2010)

(untitled) - Stebliy, M. E.; Ognev, A. V.; Samardak, A. S.; Diga, K. S.; Chebotkevich, L. A. (IEEE Trans. Magn., 2012)

OOMMF Project at NIST

(untitled) - Kim, S.-K.; Lee, K.-S.; Yu, Y.-S.; Choi, Y.-S. (Appl. Phys. Lett., 2008)

(untitled) - Stebliy, M. E.; Ognev, A. V.; Samardak, A. S.; Kolesnikov, A. G.; Chebotkevich, L. A.; Han, X. (Appl. Phys. Lett., 2014)